The Effectiveness of the Team Games Tournament (TGT) Cooperative Learning Model Supported by Digital Interactive Media: A Systematic Literature Review - Fenezia Fenezia; Armiati Armiati (Nurul Jadid University, 2025)
Education plays a pivotal role in shaping the development and sustainability of every nation, particularly in developing countries where educational advancement directly influences national progress. The Team Games Tournament (TGT) cooperative learning model has been recognized for its potential to enhance students’ academic achievement, collaboration, and engagement. However, its effectiveness can be further optimized through the integration of digital interactive media that align with contemporary learning needs. This study aims to analyze the effectiveness of the TGT learning model supported by digital media through a Systematic Literature Review (SLR) complemented by bibliometric analysis using VOSviewer. Relevant empirical studies were identified and reviewed to explore trends, research gaps, and the overall impact of TGT in digital learning environments. The findings indicate that digital-assisted TGT not only fosters active learning and motivation but also enhances critical thinking and teamwork skills. This review highlights the importance of integrating cooperative learning models with digital innovations to promote more interactive, engaging, and effective educational experiences.